Factors determining surgical outcome after bronchial re-implantation for traumatic main bronchus transection - Pulle, Mohan Venkatesh (Lung India, 2021)
OBJECTIVES: The diagnosis of traumatic transection of main bronchus is often delayed, resulting in attempts at surgical repair sometimes even months after the injury. Our aim is to analyze the factors affecting surgical outcome in patients undergoing lung preserving bronchial re-implantation for bronchial transection. MATERIALS AND METHODS: This is a retrospective analysis of prospectively maintained data of 10 cases of traumatic transection of main bronchus who underwent bronchial re-implantation at a tertiary thoracic surgery center in India. Patients were divided into two groups based on their total length of hospital stay. Occurrence of postoperative complications and/or hospital stay >7 days were considered poor surgical outcomes. RESULTS: Out of 10 patients, 6 were left main bronchus transections and 4 right main bronchus transections. The male-female ratio was 7:3. Right-sided bronchial injury and higher preoperative Injury Severity Score (ISS) were associated with poor surgical outcomes (P < 0.01). These patients also had significantly higher anastomotic complications, chest tube duration, and prolonged postoperative air leak. Age of the patient, preoperative hemoglobin or albumin levels, and time of referral did not influence the surgical outcomes. CONCLUSIONS: Poorer surgical outcomes were observed in patients who had right-sided main bronchus injury and higher ISSs. Time of referral did not influence the outcome. This study is limited by small sample size and retrospective nature. As no single center will have large numbers of this uncommon injury, multicenter pooled data are needed to re-affirm the findings of this study.